Prognostic Factors In Breast Cancer. With Special Reference to Cyclins A, B1, D1 and E, MMP-1 and Decorin - Boström, Pia (Annales Universitatis Turkuensis D 1147, 2014)
Breast cancer is a highly heterogenous malignancy, which despite of the similar histological type shows different clinical behaviour and response to therapy. Prognostic factors are used to estimate the risk for recurrence and the likelihood of treatment effectiveness. Because breast cancer is one of the most common causes of cancer death in women worldwide, identification of new prognostic markers are needed to develop more specific and targeted therapies. Cancer is caused by uncontrolled cell proliferation. The cell cycle is controlled by specific proteins, which are known as cyclins. They function at important checkpoints by activating cyclin-dependent kinase enzymes. Overexpression of different cyclins has been linked to several cancer types and altered expression of cyclins A, B1, D1 and E has been associated with poor survival. Little is known about the combined expression of cyclins in relation to the tumour grade, breast cancer subtype and other known prognostic factors. In this study cyclins A, B1 and E were shown to correlate with histological grade, Ki-67 and HER2 expression. Overexpression of cyclin D1 correlated with receptor status and non-basal breast cancer suggesting that cyclin D1 might be a marker of good prognosis. Proteolysis in the surrounding tumour stroma is increased during cancer development. Matrix metalloproteinases (MMPs) are proteolytic enzymes that are capable of degrading extracellular matrix proteins. Increased expression and activation of several MMPs have been found in many cancers and MMPs appear to be important regulators of invasion and metastasis. In this study MMP-1 expression was analysed in breast cancer epithelial cells and in cancer associated stromal cells. MMP-1 expression by breast cancer epithelial cells was found to carry an independent prognostic value as did Ki-67 and bcl-2. The results suggest that in addition to stromal cells MMP-1 expression in tumour cells control breast cancer progression. Decorin is a small proteoglycan and an important component of the extracellular matrix. Decorin has been shown to inhibit growth of tumour cells and reduced decorin expression is associated with a poor prognosis in several cancer types. There has been some suspicion wheather different cancer cells express decorin. In this study decorin expression was shown to localize only in the cells of the original stroma, while breast cancer epithelial cells were negative for decorin expression. However, transduction of decorin in decorin-negative human breast cancer cells markedly modulated the growth pattern of these cells. This study provides evidence that targeted decorin transduction to breast cancer cells could be used as a novel adjuvant therapy in breast malignancies.